Membumikan Dakwah Berbasis Komunikasi Profetik Di Era Media Baru - Qurrota A'yuni (Institut PTIQ Jakarta, 2019)
As a means of disseminating information, a new era of media does not always have a positive impact on the purpose of da’wah. The new era’s media actually raises the birth of da’wah that is extreme, radical and far from the meaning of Islam as a religion of peace. Very few da’wah actors and activists have integrated prophetic ethics and values in the new media era. They use many utterances of hatred (hatespeech) and lies (hoaxes) to preach. This phenomenon is very inversely proportional to the teachings of friendly and peaceful Islam as did the Prophet Muhammad. Therefore, grounding prophetic-based tabligh activities is very urgent in the new media era.